Analisis Pengaruh Kepemimpinan dan Motivasi terhadap Kinerja Pegawai pada PT. Asuransi Jiwa Great Eastern Palembang - Indri Ariyanti; Dedy Rusdyanto (MANAJEMEN INFORMATIKA, 2009)
The Analysis of the influence Leadership and Motivation towards the employees’ working performance at PT. Asuransi Jiwa Great Eastern Palembang. This research is done to find out the influence of Leadership and Motivation to wards employees’ working performance both partially and wholly. There are two variable groups in this research : Independent Variable, which includes Leadership (X1) and Motivation (X2) as its indicators, and Dependent Variable, which includes Working Performance (Y). Next, the methods used in the research are descriptive and causal. There are 32 employees of PT. Asuransi Jiwa Great Eastern Palembang that are included in the population and the data collection technique used is by distributing questioners. To measure the relationship between variables used, the writeuses both simple linear regression analysis equipment and double linear regression analysis equipment. Based on the result of the regression analysis, it shows that there is a significant influence of Leadership and Motivation to wards the emlpoyees’ working performance at PT. Asuransi Jiwa Greats Eastern Palembang both individually and wholly. Hence, the improvement in the quality of leaders and the employees’ motivation will be able to increase working performance at PT. Asuransi Jiwa Great Eastern Palembang.